Morphine use in the last six days of life of patients with HIV/AIDS at the inpatient unit of a South African hospice implementing the ICHC model - R. Els; H.M. Power (South African Family Practice)
Background: Seventy-five per cent of the world's HIV/AIDS population resides in Sub-Saharan Africa. South Africa, along with the rest of Sub-Saharan Africa, is experiencing an increasing disease and palliative care burden as a result of the HIV/AIDS pandemic. At present there is no cure for AIDS and access to antiretroviral treatment is limited. HIV/AIDS is the largest single cause of death in South Africa, accounting for 30% of deaths in 2000. An estimated 20 000 of the approximately 5 350 000 infected South Africans receive antiretroviral treatment. To cope with the rising need for AIDS-related health services, a comprehensive, integrated approach to health care is advocated, with a shift in focus from hospital care to home-based care. The Department of Health supports a community home-based care (ICHC) model as one of five models of care. It is based on similar principles to palliative care and was piloted at seven hospices in South Africa. This study was conducted in the inpatient unit (IPU) of a hospice participating in the ICHC pilot project. This model requires that the hospice provide the overall management of the home-based care programme, as well as various forms of support. Care provision is shared between professional nurses and non-professional community-based caregivers, who are trained by Hospice. For challenging symptoms, respite or terminal care, the hospice has a six-bed IPU to which patients can be admitted for short periods. The AIDS patients admitted to the IPU of the study hospice were all cared for under the ICHC model.